2021
DOI: 10.3389/fdgth.2021.690182
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Health, Healthcare, and eHealth of People With a Low Socioeconomic Status: A Community-Based Participatory Approach

Abstract: Low socioeconomic status (SES) is associated with a higher prevalence of unhealthy lifestyles compared to a high SES. Health interventions that promote a healthy lifestyle, like eHealth solutions, face limited adoption in low SES groups. To improve the adoption of eHealth interventions, their alignment with the target group's attitudes is crucial. This study investigated the attitudes of people with a low SES toward health, healthcare, and eHealth. We adopted a mixed-method community-based participatory resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…Another promising strategy is collaboration with the social network of people with a low SES (eg, caregivers, relatives, and experts) [ 44 ]. Recent studies identified the importance of using a personal approach and connecting via existing networks (ie, community centers or ambassadors) to successfully recruit low SES populations for lifestyle interventions [ 20 , 93 ]. Furthermore, we found that social media may achieve this goal since it has a broad reach, but the lack of robust evidence makes it difficult to draw firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising strategy is collaboration with the social network of people with a low SES (eg, caregivers, relatives, and experts) [ 44 ]. Recent studies identified the importance of using a personal approach and connecting via existing networks (ie, community centers or ambassadors) to successfully recruit low SES populations for lifestyle interventions [ 20 , 93 ]. Furthermore, we found that social media may achieve this goal since it has a broad reach, but the lack of robust evidence makes it difficult to draw firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, current eHealth interventions require users to have good digital skills and a high literacy level, which are often lacking in low SES groups. Moreover, such interventions must consider their different life situations, health care needs, and eHealth expectations [ 20 ]. When eHealth interventions do not consider the needs of this target group, intervention uptake can hinder and reinforce the inequitable use of eHealth, exacerbating health inequalities [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overall high level of digital proficiency removes the potential barriers that could prevent lower socioeconomic segments from engaging with health programs delivered through mobile apps. In addition, among communities with the lowest socioeconomic conditions in the Netherlands, there is a positive attitude toward web-based lifestyle programs [ 47 ]; this, combined with the high digital skills, potentially facilitates the adoption of the mobile app of the health program.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to offer instruction and support services, especially for middle-aged and older patients to boost patient engagement [ 28 ]. But the eHealth behavior is not only influenced by SES variables, as points out the study of Faber et al [ 29 ], which details the importance of eHealth interventions being aligned with the person’s attitude. Such research, which investigates the eHealth attitudes of people living in a neighborhood with low SES, identify two general attitudes.…”
Section: Discussionmentioning
confidence: 99%